PENGARUH RASIO KEUANGAN DAN INSENTIF PAJAK TERHADAP KINERJA KEUANGAN PERUSAHAAN PERTAMBANGAN SUBSEKTOR BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2022 - Virgianti, Leli Eka; Hanun, Nur Ravita (AKUNTANSI DEWANTARA, 2024)
Coal companies are one of the industrial companies that have opportunities for local and national economic development, so many investors are interested in investing in these companies. This study aims to examine the effect of financial ratios and tax incentives on the financial performance of coal subsector mining companies listed on the Indonesia Stock Exchange for the period 2016-2022. This study uses purposive sampling method for sampling. The data obtained in this study were 6 coal companies used as research samples with the observation period during 2016-2022. The data source used in this study comes from the Indonesia Stock Exchange web. The data analysis technique in this study used multiple linear regression analysis with the help of SPPS 23. The results of this study are Liquidity Ratio, Leverage, Activity, and Tax Incentives simultaneously have a significant effect on financial performance, while partially Liquidity Ratio, Activity has a positive and significant effect on financial performance. Furthermore, the Leverage Ratio and Tax Incentives have a significant negative effect on financial performance. Keyword : Coal Company, Financial Ratios, Tax Incentives, Financial Perfomance